Kasık Fıtığı Olan Çocuklarda Doğumsal Kalp Hastalığı Sıklığı - Kazez, Ahmet; Özel, Şeyhmus Kerem; Yılmaz, Erdal; Hanbeyoğlu, Alpaslan; Köseoğulları, Ayşe Aysel (Fırat University, 2005)
Amaç: Kasık fıtığı (KF) çocuklarda en sık yapılan ve günübirlik elektif cerrahi uygulanan bir hastalıktır. Bu çalışma, KF ve doğumsal kalp hastalığı (DKH) birlikteliğinin sıklığını saptamak için yapıldı. Gereç ve Yöntem: Ocak 2002- Aralık 2003 tarihleri arasında Çocuk Cerrahisi Kliniği'nde 192 hasta KF nedeni ile ameliyat edildi. Bulgular: Sekiz hastada (% 4.2) kalpte üfürüm belirlendi ve bunların da dördünde (% 2.1) DKH olduğu tespit edildi. KF' li hastalarda DKH sıklığı normal popülasyonun iki katı olarak bulundu. Sonuç: KF'li hastalarda kardiyak muayene dikkatli yapılmalı, şüpheli hastalarda pediatrik kardiyoloji konsültasyonu önerilmelidir.©2005, Fırat Üniversitesi, Tıp Fakültesi

Objectives: Inguinal hernia (IH) repair is the most frequent day-case elective surgery in children. The aim of this study is to determine the incidence of congenital heart disease (CHD) associated with IH. Materials and Methods: One hundred ninety-two patients have been operated for IH in our clinic between January 2002 and December 2003. Results: Heart murmur was defined in 8 patients (4,2 %) and CHD was found in 4 of these patients (2,1 %). The incidence of CHD in IH patients was found to be twice as much as seen in normal pediatric population. Conclusion: Cardiac examination should be done carefully in IH patients and pediatric cardiology consultation should be preferred in suspected cases.©2005, Fırat Üniversitesi, Tıp Fakültesi
The Incidence of Congenital Heart Disease in Children with Inguinal Hernia